Pola Pemilihan Agama Anak dalam Pernikahan Beda Agama - Zahrotul Abidah; Rohmah Maulidia; Lukman Santoso (Institut Agama Islam Negeri Ponorogo, 2025)
This study examines the pattern of children’s religious choice in interfaith families in Klepu Village, Sooko District, Ponorogo Regency. The phenomenon of interfaith marriage often raises issues of religious identity among children, especially when they reach adulthood and begin to determine their own beliefs. This research aims to analyze the emerging patterns of children’s religious selection and to explore the implications of these choices for their personal, social, and legal lives. The study employs a qualitative method with Edmund Husserl’s phenomenological approach to understand the subjective experiences of children within social and religious contexts. Primary data were obtained through interviews and observations with children from interfaith marriages, while secondary data were drawn from documents and supporting literature. The findings reveal three main patterns of religious choice among children: environmental factors influenced by peer groups; paternal factors characterized by authoritarian discipline; and maternal factors emphasizing affection, moral teaching, and religious exemplarity. These patterns have implications for children’s religious identity formation, social stability, and legal rights within the societal system. This type of research is field research. To answer the questions in this study, the author uses a phenomenological approach to understand the subjective experience of individuals in facing a phenomenon by Edmund Husserl. This thesis uses a qualitative method, while in collecting primary data the author conducted observations and interviews. While the author obtained secondary data from various other sources to complete the research needs. This research was conducted in Klepu Village, Sooko District, Ponorogo Regency, which was determined using a random technique. This study suggests that three patterns of religious selection were found, namely, first, Environmental Factors which are motivated by the invitation of friends around them. Second, Father factors which are motivated by the invitation of the father who is authoritarian and disciplines his child to worship according to his father's religion. And third, Mother factors which are motivated by the mother being a source of survival for children as well as a moral teacher and role model for her children. The implications related to the pattern of children's religious selection can be seen from the child's side, social level, and legal rights that must be borne by children from interfaith marriages.